A comparative study on the marginal integrity of two commercially available brands of calcium hydroxide liners in vitro - Oviedo, Marlene Imelda V.; Paje, Leida D.R.; Lara, Teresita C. (Adviser).; Malabanan, Ma. Rosario S. (Adviser).
Autoradiographic procedures revealed that Life is more marginally stable than Dycal after acid-etching. This due to a resin present in Life and not found in Dycal which forms a chelation reaction between the base paste and catalyst in Life, thus results in a set material which makes the product resistant to the acid etchant during a 60 sec. application.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Calcium hydroxide; Dentistry